Structured Educational Program and Peripheral Intravenous First-Time Insertion Rate in Saudi Arabia - Nicanor M. Domingo III; Leila Collantes (Universitas Jambi, Indonesia, 2020)
Peripheral intravenous insertion (PIV) is one of the most common clinical procedures which nurses receive little formal training. It is said that more than a quarter of first-time insertion rate (FTIR) fail (Hess 2010), thus, patient experience is at risk if this is not performed by a trained staff. This study aimed to explore if a Structured Educational Program (SEP) was effective to increase a hospital’s FTIR which has a failing international benchmark scores. It used a quasi-experimental design and pre-experimental one-group pretest post-test to examine the pre and post-test data set among 160 respondents. It was found out that the most of respondents are Filipinos in their 30’s who have bachelor’s degree. They have a decade or less of experience; have had no PIV training in their home country; and have less than five daily insertions. It was revealed that the SEP was effective knowledge and skills improvement. Ages, nationality, years of experience, and specialization were found to be related to improve knowledge; while nationality, licensure exam ratings, frequency of PIV insertions, and relevant trainings were associated on an enhanced skill.